발효방법에 의한 감염가금의 분해 및 발효소독 특성에 관한 연구 - 홍종태; 유병기; 김혁주; 이성현; 박경석; 오권영; 김대근; 이진주; Hong, J.T; Yu, B.K; Kim, H.J; Lee, S.H; et al. (축산시설환경학회지, 2010)
Recently, the treatment of dead poultry has become more important issue because, the infected poultry, which was buried under the ground, causes environmental contaminations such as steep water and reek occurrence, etc. Therefore, in this study, we investigated the type of treatment and the composting methods influencing to the characteristics on decomposition and fermentative disinfection of dead poultry with poultry manure and sawdust. The results of the port tests showed that amputated poultry treated by the cut-sterilization were not only more decomposed, with less smell compared to the non-treated poultry carcass. When we treated thermophilic microorganism such as bacillus in this amputated poultry, the temperature of treated poultry increased much fester, the fermentation temperature didn't rise and not maintained constantly for long time due to the small size of the fermentation port. On the other hand, we did fermentation test by the layered disposal method with more poultry. In this experiment, the temperature of fermented poultry rose to $54^{°}C$ in a day and maintained around $55^{°}C$ during four weeks period. With less odor outside the experiment room. further. Also, we inoculated AI virus, ND virus in the excrement for studying the effect of fermentative disinfection. The result of the test revealed that AI virus was destructed within 60 minutes and ND virus was destructed within 30 minutes at the temperature of $56^{°}C$. Therefore, the investigations revealed scope of composting method for steam sterilized infected poultry in the originated area mixed with poultry manure, sawdust by thermophilic microorganism could increase the effectiveness of fermentative disinfection and decrease the environmental contamination. 전염병발생 감염가금 매몰처리방법은 침출수 및 악취발생 등 환경오염의 원인이 되고 있어 폐사가금의 처리문제가 중요한 현안으로 대두하고 있다. 본 연구에서는 친환경 처리방법으로 감염가금 처리형태와 계분, 톱밥 등을 혼합한 퇴비화방법이 분해특성 및 발효 소독에 미치는 영향을 분석하였다. 연구결과, 소형 포트시험에서 가금 통처리에 비해 가금을 절단살균 처리한 경우 분해가 잘 되고 악취발생도 상대적으로 적게 나타났으며, 여기에 고온성 미생물을 처리한 경우 조기에 온도는 상승되었으나, 발효포트 규모가 소형으로 온도상승 및 온도지속기간이 길지 않았다. 그러나 절단살균한 가금처리량을 증대하여 중층처리법에 의한 발효시험결과 1일 만에 $54^{°}C$까지 온도가 상승되고 이후 4주간 $55^{°}C$ 이상 유지되었고, 분해도 잘 되었으며 악취발생도 하우스 외측에서는 경미하게 느끼는 정도인 것으로 나타났다. 또한 발효소독 효과를 알아보기 위하여 AI, ND를 분변에 접종하여 $56^{°}C$ 조건에서 바이러스의 증식여부를 조사한 결과 AI virus의 경우 60분 처리, ND의 경우 30훈 처리 이후 생존이 인정되지 않았다. 따라서 전염병 발생지역에서 가금류를 현지 살균한 후 사육장내의 분변, 톱밥 등을 혼합하여 퇴비화한다면 환경오염을 줄이고 발효소독 효과도 높일 수 있을 것으로 예상되어 금후 관련분야에서 퇴비이용 작물재배 적응성, 안전성 등 관련연구가 필요할 것으로 판단된다.